Evaluation of general joint laxity, shoulder laxity and mobility in competitive swimmers during growth and in normal controls - Jansson, A.; Saartok, T.; Werner, S.; Renström, P. (Scandinavian Journal of Medicine & Science in Sports, 2005)
The aim of the study was to evaluate differences between competitive swimmers and a reference group of school children concerning general joint laxity, laxity of the glenohumeral joint and range of motion in the shoulder. Materials and methods. Competitive swimmers (n=120) were compared with references consisting of age and gender matched school children (n=1277). General joint laxity was evaluated with the Beighton score. Anterior glenohumeral laxity was assessed according to the drawer test, and inferior glenohumeral laxity according to the sulcus test. Shoulder rotation was measured with a goniometer.